Wireless interconnect for future ULSI - Islam, Fahmida; Sultana, Samiha; Sultana, Maria (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.